PEMBERDAYAAN EKONOMI MASYARAKAT DESA CIBUNTU KECAMATAN CIAMPEA KABUPATEN BOGOR: PEMBERDAYAAN EKONOMI MASYARAKAT DESA CIBUNTU KECAMATAN CIAMPEA KABUPATEN BOGOR - muzhir ihsan ihsan; ima rahmawati; reva luthfiyah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2026)
This community service article reports a face-to-face training program held on 26–28 January 2026 in Cibuntu Village, Ciampea District, Bogor Regency, West Java. The participants were local MSME actors and home-based food processors in the village. The program aimed to improve participants’ knowledge and skills in strengthening the marketing quality of home-processed products and MSMEs. The implementation stages included socialization, pretest, material delivery, practice and mentoring, posttest, and evaluation. Based on observation, activity documentation, and evaluation sheets, the program improved participants’ understanding of branding, packaging, digital promotion, and simple business bookkeeping. This activity shows that practical and contextual assistance can support village economic empowerment and strengthen small-scale community businesses.